2018
DOI: 10.1155/2018/6734809
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori Infection on Serum Lipid Profile

Abstract: Background Some studies suggest a significant relationship between Helicobacter pylori infection and atherogenesis; but the mechanism of the relationship is almost unknown. The current study aimed at evaluating the relationship between H. pylori infection and serum lipid profile. Patients and Methods The current study was conducted on 2573 patients, from 2008 to 2015. The serum anti-Helicobacter pylori antibody titer and serum lipid profile were assessed in the study population; data were statistically analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 29 publications
1
15
0
1
Order By: Relevance
“…Among such extragastric disorders, an effect of H. pylori on the lipid profile is one of the most important concerns, especially when considering the very high prevalence of H. pylori infection and dyslipidemia all over the world [8]. In recent years, several studies have reported that H. pylori infection is associated with the serum lipid profile [9][10][11], but these findings are considered controversial. Concerning the association between H. pylori infection and serum lipid profile, we speculate several mechanisms may be responsible for changes in blood lipid regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Among such extragastric disorders, an effect of H. pylori on the lipid profile is one of the most important concerns, especially when considering the very high prevalence of H. pylori infection and dyslipidemia all over the world [8]. In recent years, several studies have reported that H. pylori infection is associated with the serum lipid profile [9][10][11], but these findings are considered controversial. Concerning the association between H. pylori infection and serum lipid profile, we speculate several mechanisms may be responsible for changes in blood lipid regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Complex pathomechanisms may be involved in the relationship between H. pylori and cortical thinning. Increased metabolic syndrome [43][44][45][46] and vascular disorders [2] due to H. pylori infection were previously suggested [47,48]. Others suggested the chronic in ammation induced by persistent H. pylori infection could produce CRP and proin ammatory cytokines [49] that could directly damage neurons or activate neuroin ammatory cascades leading to Alzheimer's disease [9].…”
Section: Discussionmentioning
confidence: 97%
“…An experimental study showed that H. pylori ‐infected mucosa produced interleukin‐8 in levels exceeding the normal range 36 . Production of interleukin‐8 in H. pylori infection results in mucosa stimulation by oxidized LDL and monocytes, which subsequently increases the immigration of T lymphocytes to smooth muscle cells 37,38 . An in vitro study showed that H. pylori can increase cholesterol absorption from egg yolk and serum, indicating that cholesterol binding to H. pylori can reduce the absorption of dietary cholesterol 38,39 .…”
Section: Discussionmentioning
confidence: 99%
“…Production of interleukin‐8 in H. pylori infection results in mucosa stimulation by oxidized LDL and monocytes, which subsequently increases the immigration of T lymphocytes to smooth muscle cells 37,38 . An in vitro study showed that H. pylori can increase cholesterol absorption from egg yolk and serum, indicating that cholesterol binding to H. pylori can reduce the absorption of dietary cholesterol 38,39 . Therefore, further research is needed to clarify the mechanisms underlying the role of H. pylori in the pathogenesis of dyslipidemia.…”
Section: Discussionmentioning
confidence: 99%